Plasma dynamic synthesis of dispersed metal oxide materials in CO2 medium; Ceramics International; Vol. 49, iss. 21 - Shanenkov I. I. Ivan Igorevich; Tsimmerman (Cimmerman) A. I. Aleksandr Igorevich; Nassyrbayev (Nasyrbaev) A. Artur; Nikitin D. S. Dmitry Sergeevich; Tabakaev R. B. Roman Borisovich; Sivkov A. A. Aleksandr Anatolyevich (2023, 2023)
Title screen